2017
DOI: 10.4238/gmr16029695
|View full text |Cite
|
Sign up to set email alerts
|

Selection of candidate reference genes and validation for real-time PCR studies in rice plants exposed to low temperatures

Abstract: Rice is a cereal that presents a great ability to adapt to different soil and climate conditions. However, as it is a tropical crop with C3 metabolism, it performs better in warm temperatures with high solar radiation. Tolerance to stress caused by low temperatures is a highly complex process that involves various metabolic pathways and cellular compartments, resulting in general or specific effects on plant growth and development. In order to observe the true effect of a particular stress on genetic expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The UBQ gene belongs to the ubiquitin gene family, which affects many important biological processes, including cell cycle regulation, growth and apoptosis, signal transduction, and immune responses. Because of its high sequence homology and the fact it is highly conserved, UBQ has been used as a reference gene for rice 36 , black fungus 37 , and cucumber 32 . Our data also indicated that TUB was the most stably expressed reference gene for the H 2 O 2 and drought treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The UBQ gene belongs to the ubiquitin gene family, which affects many important biological processes, including cell cycle regulation, growth and apoptosis, signal transduction, and immune responses. Because of its high sequence homology and the fact it is highly conserved, UBQ has been used as a reference gene for rice 36 , black fungus 37 , and cucumber 32 . Our data also indicated that TUB was the most stably expressed reference gene for the H 2 O 2 and drought treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The UBQ gene belongs to the ubiquitin gene family, which affects many important biological processes, including cell cycle regulation, growth and apoptosis, signal transduction, and immune responses. Because of its high sequence homology and the fact it is highly conserved, UBQ has been used as a reference gene for rice [36], tomato [37], and cucumber [38]. Our data also indicated that TUB was the most stably expressed reference gene for the H2O2 and drought treatments.…”
Section: Discussionmentioning
confidence: 55%
“…There is, however, no universal reference gene suitable for all species or experimental conditions [34]. Although many studies have assessed reference genes in different tissues and development stages of rice plants, and after subjecting plants to different kinds of stress [28,[35][36][37][38][39][40][41], to the best of our knowledge, no one has attempted to identify stable reference genes in the leaves of SRBSDVinfected rice plants.…”
Section: Discussionmentioning
confidence: 99%
“…We also found UBQ10 and EF1α to be reliable reference genes in the leaves of SRBSDV-infected rice plants. EF1α has been identified as a stable reference gene in rice subject to low temperatures [36], and UBQ10 has been recommended as a reliable reference gene in rice plant leaves subject to salt stress [28]. GAPDH is commonly regarded as the "classical" reference gene [45], and has been suggested as a reliable reference gene in rice seedlings suffering from iron toxicity [35].…”
Section: Discussionmentioning
confidence: 99%